Ecological Analysis of a Tourism Business Network - Toca Torres, Claudia Eugenia; Carrillo Rodríguez, Jesús (Review of Business Management, 2015)
Objective – Institutionalism as an adaptation theory has contributed to understanding of the changing characteristics in governance structures. At the same time, community ecology has enhanced the evaluation of change within organizational communities. This study aims to analyze the relations and interactions of a business network, using institutional ecology concepts. Design/methodology/approach – We applied the methods of institutionalism, as an adaptation theory, and community ecology, as evolution theory, in a network comprised of 45 businesses. Data for the flow of resources and institutional ecology were obtained using two separate instruments (designed by the researchers). Netdraw was used to graphically represent the various layers of the network and Ucinet 6 to generate the matrices. Findings – While theory identifies information, services, decisions, solutions and money as resources, as far as the workers in the businesses researched are concerned, the first four flow naturally within the business network, but money is perceived as a resource that should always originate in the other nodes of the ecosystem. Practical implications – Network stakeholders will make decisions that both strengthen relations among the members of the institutional arrangement and support the selection of institutional contexts more favorable to performing their activities. Contributions – This is the first work that applies economicevolutionary theories in order to analyze the relations and interactions within a business network.